2020
DOI: 10.3390/polym12122863
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Conductive Polyethylene/Expanded Graphite Composites as Heat Transfer Surface: Mechanical, Thermo-Physical and Surface Behavior

Abstract: Composites of high-density polyethylene (HDPE) and expanded graphite (EG) are prepared for heat exchangers in multi-effect distillation (MED) desalination. At 50 wt.% EG loading, the thermal conductivity of HDPE was increased by 372%. Moreover, the surface wettability of the HDPE/EG composite was enhanced by corona and RF plasma treatment as demonstrated by the increase in surface free energy from 28.5 mJ/m2 for untreated HDPE/EG to 55.5 and 54.5 mJ/m2 for HDPE/EG treated by corona and RF plasma, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…In this section, the feasibility analysis is performed based on our technical results of fabricating thermal conductivity for polymer–graphite composite material published in [ 15 , 16 ]. The HDPE has been loaded up to 50 wt.% with expanded graphite (EG), and the results showed that the thermal conductivity of the composite HDPE/EG increased to 2.2 W/(m·K) [ 15 ]. In another work [ 16 ], the authors disclosed a new method of fabricating a large-size thermally enhanced thermoplastic sheet/pipe.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this section, the feasibility analysis is performed based on our technical results of fabricating thermal conductivity for polymer–graphite composite material published in [ 15 , 16 ]. The HDPE has been loaded up to 50 wt.% with expanded graphite (EG), and the results showed that the thermal conductivity of the composite HDPE/EG increased to 2.2 W/(m·K) [ 15 ]. In another work [ 16 ], the authors disclosed a new method of fabricating a large-size thermally enhanced thermoplastic sheet/pipe.…”
Section: Methodsmentioning
confidence: 99%
“…Total energy demands for the composite tube extrusion have been analyzed using an extrusion simulation software (Extruder module of the Compuplast CAE Virtual Extrusion Laboratory Software, Compuplast International, Zlín, Czech Republic). The simulator incorporates the physical/material properties (thermal conductivity, heat capacity, and viscosity) described in References [ 15 , 16 ] and assumptions of standing processing conditions (friction coefficient between screw and plastics = 0.2, and between plastics and barrel = 0.3, die pressure consumption of 20 MPa). Due to the high viscosity of highly polymer composites, the temperature profiles of 190, 220, 245, and 260 °C from the first heating zone to the die section were chosen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations